AUTOMATIC VALIDATION TECHNIQUES FOR VALIDATING OPERATION OF MEDICAL DEVICES (2009)
Techniques for validating operation of a medical device are disclosed. A data collection phase utilizes a first sensor carried by a patient to record patient parameter values indicative of conditions experienced by the patient (e.g, posture states.) Therapy parameter values describing therapy adjustments requested by the patient in response to the conditions are also recorded. Associations formed between the therapy parameter values and the patient parameter values are used to develop a closed-loop algorithm for control of an IMD having a sensor similar to the first sensor. An automated device such as a robotic arm uses the recorded patient parameter values to automatically reproduce, and to subject the IMD to, conditions present during the data collection phase. Therapy delivered by the IMD while under control of the closed-loop algorithm and while being subjected to the conditions is compared to the recorded therapy parameter values e to validate IMD operation.